2011
DOI: 10.1371/journal.ppat.1002262
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase-4 Inhibition Alters Gene Expression and Improves Isoniazid – Mediated Clearance of Mycobacterium tuberculosis in Rabbit Lungs

Abstract: Tuberculosis (TB) treatment is hampered by the long duration of antibiotic therapy required to achieve cure. This indolent response has been partly attributed to the ability of subpopulations of less metabolically active Mycobacterium tuberculosis (Mtb) to withstand killing by current anti-TB drugs. We have used immune modulation with a phosphodiesterase-4 (PDE4) inhibitor, CC-3052, that reduces tumor necrosis factor alpha (TNF-α) production by increasing intracellular cAMP in macrophages, to examine the cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 124 publications
(139 reference statements)
4
80
0
1
Order By: Relevance
“…Hematoxylin and eosin (H&E) staining of lung sec-tions showed marginal differences in cellularity upon treatment with roflumilast (see the supplemental material). Consistent with previous observations that monotherapy of TB-infected animals with a PDE4-I had no effect on bacterial burden (5,14), roflumilast monotherapy showed no antibacterial properties in vivo (Fig. 1C).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Hematoxylin and eosin (H&E) staining of lung sec-tions showed marginal differences in cellularity upon treatment with roflumilast (see the supplemental material). Consistent with previous observations that monotherapy of TB-infected animals with a PDE4-I had no effect on bacterial burden (5,14), roflumilast monotherapy showed no antibacterial properties in vivo (Fig. 1C).…”
supporting
confidence: 92%
“…The bacterium-derived intramacrophage cAMP delivered by this adenylate cyclase results in reductions of TNF-␣ production via protein kinase A and the cAMP response elementbinding protein pathway, leading to decreased immunopathology and bacterial survival (15). Although not all PDE4-Is are beneficial as adjunctive agents for tuberculosis treatment (2), roflumilast has an effect similar to that of CC-3052 in combination therapy with isoniazid (5,14). The roflumilast effect appears between weeks 4 and 8 of treatment, when rapidly dividing cells have been eliminated by INH and the remaining bacilli are found in a persistent state and are phenotypically resistant to isoniazid killing.…”
mentioning
confidence: 99%
“…PDE4 hydrolyzes cAMP and is expressed in monocytes and macrophages but not in T cells. Mice and rabbits treated with the PDE4 inhibitor CC-3052, in combination with INH, had improved resolution of lung pathology and a lower burden of M. tuberculosis compared to mice treated with INH alone (148)(149)(150). However, a separate study found that administration of the PDE4 inhibitors rolipram and cilomilast decreased survival time of M. tuberculosis-infected mice and that addition of rolipram to the standard TB treatment resulted in a higher bacterial burden than with the standard treatment alone (151).…”
Section: Ifn-␥mentioning
confidence: 99%
“…Phospohdiesterase (PDE) inhibitors, including agents currently licensed for other clinical uses such as cilostazol and sildenafil, also regulate TNF-α production through decreasing cAMP activation and have shown promising results in preclinical murine and rabbit studies [166][167][168][169][170].…”
Section: Cytokine Modulationmentioning
confidence: 99%